Intentional Fracture of Bioprosthetic Valve Frames in Patients Undergoing Valve-in-Valve Transcatheter Pulmonary Valve Replacement. (August 2018) - Shahanavaz, Shabana; Asnes, Jeremy D.; Grohmann, Jochen; Qureshi, Athar M.; Rome, Jonathan J.; Tanase, Daniel; Crystal, Matthew A.; Latson, Larry A.; Morray, Brian H.; Hellenbrand, William; Balzer, David T.; Gewillig, Marc; et al.
Abstract : Background: Percutaneous transcatheter pulmonary valve replacement (TPVR) has good clinical and hemodynamic outcomes in treating dysfunctional bioprosthetic valves (BPV) in the pulmonary position. Valve-in-valve therapy can further decrease the inner diameter (ID), potentially resulting in patient-prosthesis mismatch in patients with smaller BPVs. Methods and Results: To evaluate feasibility and outcomes of intentional BPV fracture to enlarge the pulmonary valve orifice with TPVR, 37 patients from 13 centers who underwent TPVR with intended BPV fracture were evaluated. A control cohort (n=70) who underwent valve-in-valve TPVR without attempted fracture was evaluated. BPV was successfully fractured in 28 patients and stretched in 5 while fracture was unsuccessful in 4. A Melody valve was implanted in 25 patients with fractured/stretched frame and a Sapien (XT 3) valve in 8. Among patients whose BPV was fractured/stretched, the final ID was a median of 2 mm larger (0–6.5 mm) than the valve's true ID. The narrowest diameter after TPVR in controls was a median of 2 mm smaller ( P <0.001) than true ID. Right ventricular outflow tract gradient decreased from median 40 to 8 mm Hg in the fracture group. Cases with fracture/stretching were matched 1:1 (weight, true ID) to controls. Post-TPVR peak gradient was lower but not significant (8.3±5.2 versus 11.8±9.2 mm Hg; P =0.070). There were no fracture-related adverse events. Conclusions: Preliminary experience shows intentional fracture of BPV frame can be useful for achieving larger ID and better hemodynamics after valve-in-valve TPVR. Abstract : Supplemental Digital Content is available in the text.